2007
DOI: 10.1073/pnas.0708916105
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-2 receptor accessory protein MRAP forms antiparallel homodimers

Abstract: The melanocortin-2 (MC2) receptor accessory protein (MRAP) is required for trafficking of the G protein-coupled MC2 receptor to the plasma membrane. The mechanism of action and structure of MRAP, which has a single transmembrane domain, are unknown. Here, we show that MRAP displays a previously uncharacterized topology. Epitopes on both the N-and C-terminal ends of MRAP were localized on the external face of CHO cells at comparable levels. Using antibodies raised against N-and C-terminal MRAP peptides, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
204
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 155 publications
(215 citation statements)
references
References 24 publications
7
204
2
2
Order By: Relevance
“…Surface and Total Epitope Detection by Fixed Cell ELISA-To measure epitopes on the extracellular side of the plasma membrane, cells in 12-or 24-well plates were washed with phosphate-buffered saline, fixed for 10 min with 2% paraformaldehyde, washed, blocked in 5% nonfat dry milk in phosphatebuffered saline, incubated with 1:5000 mouse monoclonal anti-HA or anti-V5 antibody in blocking buffer for 2 h at room temperature, washed three times for 5 min in phosphate-buffered saline, and incubated with secondary antibody and processed for ELISA as described (3). The same protocol was performed in permeabilized cells to measure total expression of proteins of interest.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Surface and Total Epitope Detection by Fixed Cell ELISA-To measure epitopes on the extracellular side of the plasma membrane, cells in 12-or 24-well plates were washed with phosphate-buffered saline, fixed for 10 min with 2% paraformaldehyde, washed, blocked in 5% nonfat dry milk in phosphatebuffered saline, incubated with 1:5000 mouse monoclonal anti-HA or anti-V5 antibody in blocking buffer for 2 h at room temperature, washed three times for 5 min in phosphate-buffered saline, and incubated with secondary antibody and processed for ELISA as described (3). The same protocol was performed in permeabilized cells to measure total expression of proteins of interest.…”
Section: Methodsmentioning
confidence: 99%
“…MRAP forms antiparallel homodimers, which are exceedingly rare structures, and it is these dimers that co-precipitate with the MC2 receptor (3). Mutagenic analysis has revealed that the carboxyl-terminal region of MRAP is not essential, but the amino-terminal and transmembrane regions are necessary for function (3)(4)(5).…”
mentioning
confidence: 99%
See 3 more Smart Citations